Treatment of varicocele with Fu's subcutaneous needling: A case report. Issue 38 (September 2019) - Yu, Xiaojiang; Li, Ting; Zhuang, Zhenjie; Li, Yingxian; Xie, Dongming; Li, Zikang; Yuan, Xueya; Yang, Chaojie
Abstract: Rationale: Fu's subcutaneous needling (FSN) is an innovative therapy of traditional acupuncture. FSN has been widely applied for the treatment of pain symptoms by relieving local muscle tension and promoting local blood circulation. Varicocele (VCL) is a disease that commonly occurs in male adolescents. Patients with VCL can suffer from pain in the scrotum, inguinal area, or unilateral testis, which could be an indication for FSN. In this study, we present a unique case, in which a 30-year-old male patient with VCL benefitted from FSN. Patient concerns: A 30-year-old male complained of dull pain and swelling in the testicular area for 4 months. No significant abnormalities were identified in his genitalia by physical examination. Diagnoses: The patient was diagnosed with VCL, with his symptoms and signs of dull pain and swelling in the testicular area, and ultrasound also demonstrated the left-side VCL. Interventions: FSN was performed successfully twice a week on a different day without postoperative complications. The total course lasted 8 weeks. Outcomes: The patient experienced obvious relief of his testicular pain and swelling after each treatment course. All his symptoms resolved and disappeared after 4 treatment courses. After the 8-week treatment course, the color ultrasound after treatment demonstrated improved anastomotic blood flow rates in his left spermatic vein. No narrow or thrombotic parts were observed post-treatment compared to the color ultrasound before treatment. The patient was followed up at 1, 3, and 6 months after treatment. During the follow-up period, his previous symptoms disappeared without recurrence. Lessons: FSN significantly improved the patent's symptoms of testicular pain and abnormal dilatation and tortuosity of the spermatic veins. FSN might exert its therapeutic effect by improving the relaxation of muscle oppression and increasing the local blood reperfusion to resume blood stream. Due to the limitation of a single clinical observation case, a randomized clinical trial with a sufficient follow-up time is needed.